1999
DOI: 10.1097/00005537-199903000-00017
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of contact granuloma

Abstract: The recurrence rate after surgery was high. Surgery may prolong the recovery time. Subjective symptoms diminished during voice therapy, but we cannot confirm that it was beneficial for the healing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 18 publications
1
42
0
2
Order By: Relevance
“…4,7,9,[12][13][14] Studies identifying intubation as a cause of VPG have a majority of female subjects. 5 Males are reportedly more predisposed to age-related changes of the larynx, and this may lead to more secondary hyperfunctional behaviors (muscle tension dysphonia) that exacerbate an already traumatized vocal process. 21 Perhaps, for those patients recalcitrant to medical, behavioral, and surgical treatment, an underlying etiological factor may be glottal insufficiency (e.g., vocal fold atrophy or scar).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,7,9,[12][13][14] Studies identifying intubation as a cause of VPG have a majority of female subjects. 5 Males are reportedly more predisposed to age-related changes of the larynx, and this may lead to more secondary hyperfunctional behaviors (muscle tension dysphonia) that exacerbate an already traumatized vocal process. 21 Perhaps, for those patients recalcitrant to medical, behavioral, and surgical treatment, an underlying etiological factor may be glottal insufficiency (e.g., vocal fold atrophy or scar).…”
Section: Discussionmentioning
confidence: 99%
“…These procedures can be performed in the operating room or an in-office setting. 2,[5][6][7][9][10] Previous case series have demonstrated high recurrence rates (as high as 92%) despite surgery and possibly prolonged recovery time. 5 Other forms of treatment have been proposed including antibiotics, corticosteroids, postexcision irradiation, and botulinum toxin A injection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ylitalo et al in a retrospective study suggested that the trauma of surgery may actually delay recovery. 1 Widely accepted indications for surgical treatment are airway obstruction and the need to establish a histopathologic diagnosis through biopsy. Persistent hoarseness despite appropriate non-surgical therapy is also an accepted indication for surgery.…”
Section: Mechanicalmentioning
confidence: 99%
“…Although there are still proponents for surgical removal in the absence of these indications, the weight of contemporary opinion supports nonsurgical interventions as the primary management. 47,1,23 The recommended extent of surgery needed to remove the granuloma has varied from superficial excision to deeper resection with removal of underlying cartilage. Theoretical support for more aggressive resection is offered by the work of McFerran et al, who, in 1994, examined five patients with vocal process granuloma with CT. 2 They identified increased density of the arytenoid cartilage on the side of a unilateral vocal process granuloma.…”
Section: Mechanicalmentioning
confidence: 99%